Asymptotic quadratic price game mechanism for video stream extensible feedback unloading - Qianqian GE (Dianxin kexue)
A progressive quadratic price game mechanism with scalable feedback offloading of video streams was proposed.Firstly,the congestion of cellular network could be alleviated by effectively uninstalling some video traffic from all video streaming services to Wi-Fi network,thus providing seamless video streaming services.Several physi-cal paths were integrated in an economical and efficient way.The fountain coded symbols of compressed video data were transmitted simultaneously through LTE and Wi-Fi network to flexibly control the viewing through Wi-Fi net-work and reduce the video quality degradation caused by wireless channel errors.Secondly,a progressive secondary price auction mechanism was used to allocate limited LTE resources to multiple user devices to maximize social wel-fare and achieve Nash equilibrium.The scalability and convergence of the system were verified theoretically.Finally,the performance advantages of the proposed algorithm in video streaming transmission quality and energy consump-tion were verified by experimental simulation.